Interaction with Social Robots: Social Skill Development in Children - An Atypical Study - Singh, Dr. Jagvinder (The journal of contemporary issues in business and government, 2019)
Chetah’s footsteps are being followed by technology, which is speeding forward into the era of Artificial Intelligence, where robots have become an integral part of many of our daily activities, acting as peers, facilitators, and assistants. The days when the name ’ROBOT’ was only used to refer to machines used for industrial purposes are long gone, and the time has come for humanoids to become more like friends. Almost every domain has been invaded by robots. As it is thought that robots are capable of completing jobs that are beyond human conception, they are being deployed in the realms of medical care and child care rather than managing dangerous equipment.